2009
DOI: 10.1021/jf801992s
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Quality and Bioactive Compounds with Antioxidant Activity of Tomatoes Grown On-Farm: Comparison of Organic and Conventional Management Systems

Abstract: Replicated field trials at three matched farm pairs in southern and central Taiwan were established in October 2004 and 2005 to compare fruit quality and nutritional parameters of tomatoes grown on-farm under organic versus conventional management systems in tropical and subtropical environments. Two processing tomato varieties were evaluated using a randomized complete block design at each of the farms. Aggregation of farms by type (organic vs conventional) across two years resulted in no significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
40
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 24 publications
(56 reference statements)
14
40
1
1
Order By: Relevance
“…Ascorbic acid was the most abundant antioxidant in all the samples, and the highest concentration was found in the sample of the so-called heart tomato (18.56 mg/100 g fw). The values found in the present study were similar to the ones reported on varieties from Italy (Ilahy et al, 2011) and Taiwan (Juroszek et al, 2009) (both in the order of 20 mg/100 g fw), but lower than the values found in Czech Republic (21.7-25.8 mg/100 g fw, Kotkov et al, 2011) and Spanish (39-163 mg/100 g fw; Guil-Guerrero and Rebolloso-Fuentes, 2009) varieties. The role of ascorbic acid in the prevention of diseases related to oxidative damage occurs due to its ability to neutralize the action of free radicals in the biological systems (Borguini and Torres, 2009).…”
Section: Antioxidants Compositionsupporting
confidence: 85%
See 2 more Smart Citations
“…Ascorbic acid was the most abundant antioxidant in all the samples, and the highest concentration was found in the sample of the so-called heart tomato (18.56 mg/100 g fw). The values found in the present study were similar to the ones reported on varieties from Italy (Ilahy et al, 2011) and Taiwan (Juroszek et al, 2009) (both in the order of 20 mg/100 g fw), but lower than the values found in Czech Republic (21.7-25.8 mg/100 g fw, Kotkov et al, 2011) and Spanish (39-163 mg/100 g fw; Guil-Guerrero and Rebolloso-Fuentes, 2009) varieties. The role of ascorbic acid in the prevention of diseases related to oxidative damage occurs due to its ability to neutralize the action of free radicals in the biological systems (Borguini and Torres, 2009).…”
Section: Antioxidants Compositionsupporting
confidence: 85%
“…β-Carotene was found in lower amounts than tocopherols, while lycopene was present in higher concentrations; the highest levels of carotenoids were observed in the sample from round tomato (0.51 and 9.49 mg/100 g fw for β-carotene and lycopene, respectively). The β-carotene levels found in the studied Portuguese farmer' varieties were similar to the concentration reported on varieties from Italy (Ilahy et al, 2011) and Taiwan (Juroszek et al, 2009) (~0.5 mg/100 g fw). Nevertheless, lycopene values observed in the studied samples were higher than the ones described for fresh and lyophilized samples from Taiwan (3 and 2 mg/100 g fw, respectively; Chang et al, 2006), but slightly lower than in Italian varieties (~10 mg/100 g fw; Ilahy et al, 2011).…”
Section: Antioxidants Compositionsupporting
confidence: 84%
See 1 more Smart Citation
“…Total average phenolic content was slightly higher in organic agriculture in a 3-year study (1 and 7% for the two investigated cultivars) [70]. In a 2-year study, on two cultivars, no differences were pointed out [71] and on four cultivars for 3 years no differences were found apart from the behavior of one cultivar along 2 years (one case higher under organic cultivation and in the second higher under conventional cultivation) [72]. Individual phenolic compounds of the four cultivars were analyzed using HPLC-DAD-MS/MS, and 30 polyphenols were identified and quantified; the cultivation method had generally minor impact on the content of phenolic compounds with respect to growing year and cultivar.…”
Section: Effect Of Managementmentioning
confidence: 63%
“…Farm management skills combined with site-specific effects contribute to high vitamin C levels, and the choice of variety significantly influences the content of ascorbic acid [32]. The variation in vitamin C content in tomatoes depends mainly on environmental conditions.…”
Section: Phytochemicalsmentioning
confidence: 99%